Indonesia's Energy Transition Preparedness Framework Towards 2045 (BRIN Publishing, 2024)
Energy transition is a shift in the system of energy production and consumption, from fossil-based materials (oil, natural gas, coal) to renewable energy sources (nuclear, wind, solar). Indonesia’s national energy transition roadmap has set the vision towards a cleaner and more sustainable energy future in 2045. The ultimate goal is to reach net zero emission, the state in which emissions caused by human activities are balanced by carbon dioxide removal over a certain period of time. With this vision, Indonesia stands as a beacon of promise in the global pursuit of green energy solutions, navigating the path towards a more sustainable and resilient future. Indonesia's Energy Transition Preparedness Framework Towards 2045 unveils a comprehensive framework that encapsulates Indonesia’s energy transition readiness and elaborates the steps needed to strengthen the efforts. This book represents a significant milestone in Indonesia’s commitment to foster a transition towards renewable energy. From the lush landscapes of Sumatra to the vibrant cities of Java, Indonesia’s rich diversity is mirrored in its approach to energy transition—a transformative journey that encompasses not only technological advancements, but also socioeconomic considerations, policy dynamics, and the empowerment of its people. This book will be useful for the general public to learn and understand the framework of energy transition and supplies, so that it will eventually accelerate clean energy momentum in Indonesia.